2020
DOI: 10.1007/s00264-020-04876-4
|View full text |Cite
|
Sign up to set email alerts
|

Onlay fibula autografting technique and its comparison with cortical allograft for the reconstruction of periprosthetic bone defects around the femur

Abstract: Background Bone defect around the femur related to revisions or periprosthetic fractures (PFF) is an issue. We present a bone defect reconstruction technique in femoral revisions and/or PFF using fibula autograft and compared our radiological and clinical results to that of allograft. Methods A total of 53 patients who underwent revision hip arthroplasty and/or PFF fixation with the use of cortical fibula autograft (FG group) or cortical allograft (CG group) were evaluated. After exclusions, 20 patients who ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Lastly, bone grafting should be considered for patients with poor bone stock or major femoral bone defects. Some authors have addressed the need to use cortical fibula onlay autografts in cases of poor bone stock, reporting clinical and radiological results comparable to allografts ( 60 , 61 ). Autograft incorporation would be more rapid, cost-effective, and easy to achieve without severe morbidity at the donor site than the allograft ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, bone grafting should be considered for patients with poor bone stock or major femoral bone defects. Some authors have addressed the need to use cortical fibula onlay autografts in cases of poor bone stock, reporting clinical and radiological results comparable to allografts ( 60 , 61 ). Autograft incorporation would be more rapid, cost-effective, and easy to achieve without severe morbidity at the donor site than the allograft ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, the analysis may be limited by potential publication bias. Third, all these studies were case series, and different MTTS were used for THR in PFF; this does not allow for a precise analysis of the overall survival of the different modular stems ( 60 , 62 ). However, the causes of THR were the same in all the included studies, and this systematic review provides the strongest available evidence in the literature to date.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that cortical allograft strut augmented with platelet-rich plasma could successfully treat long bone nonunions in the lower limb. Although autografts were fresh viable tissues with cancellous parts and the bone marrow, which were not only osteoconductive but also osteoinductive and osteogenic grafts, cortical allografts also have some superiority to autografts in terms of larger and longer size and more significant defects [ 7 ]. These echoed the findings of earlier research, and PRP seemed, to some extent, an attractive biological to enhance fracture healing [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cortical strut allograft was generally used for advanced age patients, severe osteoporosis, bone defect, short transverse fracture and the discontinuity of medial femoral cortex, especially the position where the plate could not be placed due to proximity to certain vessels and nerves [ 6 ]. Cortical allografts were generally larger and longer than autografts in size and, therefore, can be used in more significant defects [ 7 ]. Although allogeneic bone is not comparable to the autogenous bone in osteogenesis, bone conductivity, bone induction, and fixation stability, allogeneic bone is accessible [ 8 ].…”
Section: Introductionmentioning
confidence: 99%